Implementation of The Rehabilitation Model on Victims of Drug Abuse in The Development of The Legal System in Indonesia - Mohamad Ali Syaifudin; Abdullah Sulaiman; Vientje Ratna Multiwijaya (Pusat Publikasi Nusantara, 2023)
Drug abuse is usually initiated by the use of trial and error just following friends to reduce or eliminate pain, fatigue, mental tension, or as entertainment or for association. The problem of differences in perception in the implementation of Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, especially regarding rehabilitation for novice drug users. The purpose of this study is the regulation of the rehabilitation process for novice users or victims of drug abuse and addicts in the Indonesian legal system. The reconstruction of law enforcement in legal cases against novice users, addicts and drug abusers at this time, an ideal model for the concept of drug rehabilitation in the development of the Indonesian legal system. Using empirical legal research where a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The results of the study include the regulation of the rehabilitation process for novice users or victims of drug abuse and addicts in the Indonesian legal system, it is hoped that there will be legal reform in the Indonesian legal system where legal reform according to the author is a comprehensive and multidimensional handling effort in order to achieve maximum results, and eradication efforts must be carried out gradually, consistently, and continuously. Law enforcement reconstruction in legal cases against novice users, addicts and drug abusers at this time there is still a gap in the legal process in law enforcement in narcotics crimes, law enforcement officials, especially the Police in the assessment process against perpetrators of drug abuse, should not distinguish the social status of perpetrators who will carry out integrated assessments or examinations in terms of knowing the perpetrators as users or dealers Narcotics, according to the author, drug addicts are not real drug offenders but dealers who should be eradicated because they are the real perpetrators of crimes in narcotics because if drug addicts are not given rehabilitation forever the addict will continue to be victims of drug dependence. The ideal model for the concept of narcotics rehabilitation in the development of the Indonesian legal system is expected to have legal synchronization between 3 (three) law enforcement elements, namely the Police, the Prosecutor's Office and the Panel of Judges in the Court handling narcotics abuse cases requiring making primary or primary charges with Article 127 of the Narcotics Law. Suggestions include